2022
DOI: 10.1021/acssuschemeng.2c01652
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofiber Preparation Combined with Bioethanol Production from Fermented Sweet Sorghum Bagasse

Abstract: In order to achieve cost-competitive industrial production of cellulose nanofibers (CNFs), bioethanol extraction and lignocellulose pretreatment from fermented sweet sorghum bagasse were combined with alkaline distillation in this study. CNFs were further prepared from an alkaline-distilled substrate after washing, bleaching, and a high-pressure homogenization process. Lignin-containing cellulose nanofibers (LCNFs) were simultaneously prepared without bleaching. The effects of different alkali loadings on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Specific growth rates for Z. mobilis on glucose (0.3−0.48 h −1 ) and P. stipitis on xylose (0.22−0.28 h −1 ) have so far been reported in the literature for single cultures at low levels of sugars. 39,40,61 Similarly, specific growth rates of about 0.43 and 0.21 h −1 for Z. mobilis and P. stipitis in single glucose and xylose media were obtained in this work. However, in the sequential-co-culture fermentation, no report on the specific growth rate of individual species was available.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Specific growth rates for Z. mobilis on glucose (0.3−0.48 h −1 ) and P. stipitis on xylose (0.22−0.28 h −1 ) have so far been reported in the literature for single cultures at low levels of sugars. 39,40,61 Similarly, specific growth rates of about 0.43 and 0.21 h −1 for Z. mobilis and P. stipitis in single glucose and xylose media were obtained in this work. However, in the sequential-co-culture fermentation, no report on the specific growth rate of individual species was available.…”
Section: Resultsmentioning
confidence: 98%
“…This was a sign of the robust stability of PITB throughout the fermentation and lower bioethanol level in the culture and hence less inhibition via its in situ removal. However, some researchers reported that using pervaporation played a dominant role only at the beginning of coupling. ,,,, The stable permeation flux and separation factor of TSP could have resulted from permanent antiswelling and anti-fouling–biofouling properties during 161 h. However, they fell to average values of 30.34 and 1.73 kg/m 2 ·h in the real fermentation broth compared to the synthetic solutions (34.6 and 1.95 kg/m 2 ·h, respectively). Xue et al used self-flocculating yeast and CNT/PDMS membrane at the same time and found out that the stable performance of the integrated process significantly decreased the production cost.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chemical composition analysis of fermentation residues cited the literature data. 31 The quality of vinasse feed was analyzed according to AOAC standards. 32 ■ RESULTS AND DISCUSSION Tolerance with Sulfur Dioxide.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%